Coordinative chain transfer copolymerization of ethylene and styrene using an ansa-bis(fluorenyl) neodymium complex and dialkylmagnesium. Issue 23 (31st May 2018) - Nzahou Ottou, Winnie; Norsic, Sébastien; Poradowski, Marie-Noëlle; Perrin, Lionel; D'Agosto, Franck; Boisson, Christophe
Abstract : Coordinative chain transfer copolymerization of ethylene and styrene was successfully achieved using an ansa -bisfluorenyl neodymium complex, dialkylmagnesium as a chain transfer agent and di- n -butylether as a co-solvent. Abstract : Coordinative chain transfer copolymerization of ethylene and styrene was successfully achieved using an ansa -bisfluorenyl neodymium complex, a dialkylmagnesium as a chain transfer agent and di- n -butylether (Bu2 O) as a co-solvent. Under these conditions, a controlled chain growth was observed during the polymerization. Chain-end functionalization was performed and it revealed that both styryl and alkyl terminated chains shuttle between neodymium and magnesium. The analysis of the microstructure revealed that up to 3 mol% of styrene can be incorporated into the polymer. A computational mechanistic study at the DFT level was performed to characterize insertion selectivities and it further revealed the role of magnesium species in assisting β-H elimination.